Analisis Pengaruh Self-Esteem, Locus Of Control dan Organizational Citizenship Behavior Terhadap Kinerja Karyawan Di Fakultas Ekonomi & Bisnis Universitas Ahmad Dahlan, Dengan Employee Engagement Sebagai Variabel Moderasi - Annik Khoirunnissak; Ayudya Arifatur Niza; Permata Rizka Melati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to analyze the influence of Self Esteem, Locus of Control, and Organizational Citizenship Behavior (OCB) on employee performance at the Faculty of Economics and Business, Ahmad Dahlan University, Employee Engagement is examined as a moderating variable. Employing a quantitative approach with a sample of 32 employees, the study found that Self-Esteem has a significant positive impact on employee performance. However, Locus of Control and Organizational Citizenship Behavior (OCB) did not exhibit significant effects. Employee Engagement was found to moderate the relationship between Self-Esteem and performance, emphasizing the crucial role of employee involvement in maximizing performance. The findings imply that organizations should focus on enhancing both Self-Esteem and Employee Engagement to optimize performance. Furthermore, the study suggests the need for further exploration of the roles of Locus of Control and Organizational Citizenship Behavior (OCB) in the context of employee performance.